Impact of social-psychological factors on anxiety before gastrointestinal endoscopy and quality of life - Huang, Zhen-peng; Quan, Kong-jin; Wen, Bin-bin; Lin, Jia-feng; Liu, Tao; Yang, Li-ping; Meng, Li-ping (Frontiers in Psychiatry, 2025)
IntroductionThis study aimed to examine the impact of social-psychological factors on anxiety before gastrointestinal endoscopy and its effect on patients’ quality of life (QoL).MethodsPatients scheduled for gastrointestinal endoscopy were recruited for the study. Demographic characteristics, social factors, lifestyle information and endoscopy-related data were obtained through self-reports and the hospital information system. The 7-item Generalized Anxiety Disorder Questionnaire (GAD-7) was used to assess anxiety, while depression and somatization were evaluated using the Patient Health Questionnaire-9 (PHQ-9) and PHQ-15, respectively. Sleep quality was measured with the Pittsburgh Sleep Quality Index (PSQI), social support was assessed using the Social Support Rating Scale (SSRS), and QoL was evaluated through the 12-item Short Form Survey (SF-12).ResultsThe prevalence of anxiety before gastrointestinal endoscopy was 34.44%. Gender, age, sleep quality, social support, depression, and somatization were associated with anxiety (all P<0.05). Independent predictors of anxiety were gender, age, PSQI, SSRS, PHQ-9 and PHQ-15 scores (all P<0.05). Furthermore, PSQI, PHQ-9, and PHQ-15 scores were positively correlated with the severity of anxiety (all P<0.05). Patients with anxiety exhibited lower scores in domains of the SF-12, including general health (GH), physical functioning (PF), role-physical (RP), bodily pain (BP), role-emotional (RE), mental health (MH), vitality (VT), and social functioning (SF). Both physical component summary (PCS) and mental component summary (MCS) scores were reduced. Notably, GH, RP, RE, MH, VT, SF, and MCS scores were negatively correlated with varying levels of anxiety (all P<0.05).ConclusionSocial-psychological factors play a role in anxiety before gastrointestinal endoscopy; anxiety can negatively affect patients’ QoL.